ANALISIS PENERAPAN LEAN MANUFACTURING PADA PROSES PAINTING DI PT CATERPILLAR INDONESIA BATAM - Hendrawan, Rizko; Tarigan, Elsya Paskaria Loyda (LPPM Universitas Putera Batam, 2025)
PT Caterpillar Indonesia Batam, a subsidiary of Caterpillar Inc., faces challenges in the painting process of the 6020-excavator chassis, characterized by a high rejection rate and prolonged waiting time between the painting and assembly departments. This study aims to identify the root causes of defects in the painting process and propose solutions to minimize product rejection and improve production flow. The analysis utilizes a fishbone diagram, covering factors related to manpower, methods, machines, and materials. The findings indicate that the primary causes of defects include inexperienced operators, incorrect sanding techniques, damaged spray guns, clogged pump sprayers, and improper material mixing. To address these issues, several improvements are proposed, including regular operator training, refinement of standard operating procedures (SOPs), preventive maintenance for painting equipment, and better raw material preparation. The Value Stream Mapping analysis reveals a lead time reduction of 3,000 seconds, from 72,360 to 69,360 seconds, leading to an increase in process cycle efficiency from 75.8% to 79.1%. These improvements enhance production flow, reduce waste, and optimize the overall painting process.